Karakteristik Tepung Jewawut yang Difermentasi dengan Bimo CF pada Lama Fermentasi yang Berbeda - Cicilia, Siska; Basuki, Eko; Alamsyah, Ahmad; Yasa, I Wayan Sweca; Unsunnidhal, Lalu; Jannah, Nuzuliya Miftahul (Fakultas Teknologi Pangan dan Agroindustri, Universitas Mataram, 2024)
Millet is a cereal with high nutritional content and has the potential to be a substitute for wheat. This research aimed to determine the characteristics of millet flour fermented by Bimo CF at different fermentation times. This research was conducted using a completely randomized design with one factor (fermentation time). It consisted of P1 (0 hours), P2 (12 hours), P3 (24 hours), P4 (36 hours), and P5 (48 hours). The resulting product of each treatment's water content, ash content, crude protein content, lightness, and yield were analyzed as tested parameters. Observation data were analyzed using ANOVA and further tested using Honest Significant Difference Test at a significance level of 5%. The result showed that fermentation period treatment using Bimo CF starter had a significantly different effect on water, ash, crude protein content, lightness, and yield. The 12-hour fermentation treatment is the recommended treatment to produce fermented millet flour, with a water content of 2.78%, ash content of 2.41%, crude protein content of 7.41%, lightness of 73.11, and yield of 45.5%.